Psoralen Induces Developmental Toxicity in Zebrafish Embryos/Larvae Through Oxidative Stress, Apoptosis, and Energy Metabolism Disorder - Xia, Qing; Wei, Lingying; Zhang, Yun; Kong, Haotian; Shi, Yongping; Wang, Xue; Chen, Xiqiang; Han, Liwen; Liu, Kechun (Frontiers in Pharmacology, 2018)
Psoralen toxicity is an issue of wide concern. However, an assay for psoralen-induced developmental toxicity has not been reported to date. Moreover, the underlying mechanism of psoralen-induced developmental toxicity is unclear. Therefore, this study attempted to develop a psoralen-induced developmental toxicity assay in zebrafish embryos/larvae. Psoralen treatment caused a decrease in the hatching rate and body length and a significant increase in the malformation rate of zebrafish. Yolk retention, pericardial edema, swim-bladder deficiency, and curved body shape were also observed after psoralen treatment. Yolk retention might have been caused by an abnormality in lipid metabolism. Further experiments indicated that psoralen exerted toxic effects on the developing heart, liver, macrophages, and nervous system. Increased generation of reactive oxygen species, inhibition of total superoxide dismutase activity, and increased malondialdehyde concentrations indicated inhibition of antioxidant capacity and the presence of oxidative stress. A greater number of apoptotic cells were observed after psoralen exposure, relative to the control. Furthermore, the results of gene-expression analysis showed that psoralen induced developmental toxicity by means of oxidative stress, apoptosis, and energy metabolism abnormalities. These findings will be helpful in understanding psoralen-induced toxicity.